Capital Structure and Thin-capitalization Rule: Case study of parent companies in Slovenia - Hauptman , Lidija; Tič, Sašo (Naše gospodarstvo/Our economy, 2014)
Theory defines the quality of a capital structure in different ways, and many factors have an impact on it. In the case of loans between the related parties (as a form of debt financing) and the savings that can be achieved using this form of financing, the companies create a so-called tax shield, by which exploitation is restricted by the thin capitalization rules in many countries. In this paper, the changes in the capital structure of selected parent companies in Slovenia for the 1997–2012 period were analyzed. The survey reveals that the proportion of debt financing increased after the adoption of the thin capitalization rules in 2004 and despite its escalation.